Predictive Value of the Age, Creatinine, and Ejection Fraction (ACEF) Score in Patients With Acute Fulminant Myocarditis - Liu, Lin; Yang, Xinyu; Gu, Yiyu; Jiang, Tingbo; Xu, Jialiang; Xu, Mingzhu (Frontiers in Physiology, 2021)
Objective: Patients with acute fulminant myocarditis often have more adverse cardiovascular events and higher mortality. The purpose of this study was to evaluate the usefulness of age, creatinine, and left ventricular ejection fraction (ACEF score), in determining the risk that acute fulminant myocarditis will lead to serious cardiovascular events, death, and cardiac dysfunction. Methods: We retrospectively reviewed the demographics, laboratory tests, medications, echocardiographic examinations, in-hospital clinical outcomes, major adverse cardiovascular events (MACE), and survival rate at one year in the medical records of 220 consecutive subjects suffering from acute fulminant myocarditis from January 2013 to June 2019. Results: 220 patients were divided into a survivor group and a non-survivor group. This study found that patients in the non-survivor group were older, had higher heart rates, and had more serious injuries to multiple organ functions. A high ACEF score at admission was independently associated with an unfavorable prognosis, and it was a predictor of in-hospital mortality. The current analysis extends the predictive performance of the ACEF scores at 30 days by evaluating echocardiographic data as applied to survivors of fulminant myocarditis and cumulative rates of MACE at one year. The results indicated that patients with high ACEF scores had poor recovery of cardiac function, and higher rates of MACE, all-cause death, and heart failure at 1-year than the low-ACEF group. Conclusion: The ACEF score was identified as an effective predictor of poor in-hospital outcomes, worse cardiac recovery after 30 days, and higher rates of MACE, all-cause death, and heart failure at 1-year in patients who had acute fulminant myocarditis. These data suggest that its predictive accuracy means the ACEF score could be used to assess the prognosis of patients with acute fulminant myocarditis.